Echocardiographic assessment of blood flow volume in the superior vena cava and descending aorta in the newborn infant. Issue 1 (11th July 2007) - Groves, A M; Kuschel, C A; Knight, D B; Skinner, J R
Abstract : Background: Clinical methods of assessing adequacy of the circulation are poor predictors of volume of blood flow in the newborn preterm. Doppler echocardiography can be used to assess perfusion at various sites in the circulation. Objective: To assess repeatability of measurement of volume of superior vena caval (SVC) and descending aortic (DAo) flow. Design: SVC and DAo flow volume were assessed four times in the first 48 h of postnatal life in a cohort of preterm (<31 weeks) infants. Within-observer and between-observer repeatability was assessed in a subgroup of preterm infants. Normative values were derived from 14 preterm infants who required <48 h respiratory support and 13 healthy term infants. Results: Within-observer repeatability coefficient was 30 ml/kg/min for quantification of SVC flow, and 2.2 cm for DAo stroke distance. Measurement of DAo diameter had poor repeatability. Between-observer repeatability appeared poorer than within-observer repeatability. The fifth centile for volume of SVC flow in healthy preterm infants was 55 ml/kg/min and 4.5 cm for DAo stroke distance. Conclusions: Echocardiographic assessments of volume of SVC flow and velocity of DAo flow have similar within-observer repeatability to other neonatal haemodynamic measurements. Between-observer repeatability for both measurements was poor, reflecting the difficulty of standardising these novel techniques. In this small cohort of preterm infants, SVC flow volume <55 ml/kg/min and DAo stroke distance <4.5 cm represented low or borderline systemic perfusion in the first 48 h of postnatal life.